Spatial disparities in human development : perspectives from Asia - Kanbur, Ravi (ed.) (Tokyo, 2006)
Spatial disparities are a measure of the unequal distribution of income, wealth, power and resources between peoples in different locations. As a dimension of overall inequality, spatial disparities have added significance when combined with regional divisions and political and ethnic tensions that can undermine social and political stability. This book focuses on issues of poverty and inequality that are directly related to the Millennium Development Goals. The authors examine spatial disparities in countries and regions that are attracting considerable professional and political attention, such as China, Russia and Central Asian countries.
Keywords: Poor-Asia-Case studies